Chad : The Economic Benefits of a Post-COVID-19 Gender-Equitable Society - World Bank (World Bank, Washington, DC, 2021)
This report examines the extent of gender gaps and their economic impact in Chad. It proposes policies for improving gender equality, taking into account the challenges posed by COVID-19. Although the Government of Chad has taken actions designed to boost gender equality, significant challenges persist. Child marriage is widespread among girls, reducing girls’ education and resulting in one of the highest rates of early childbearing worldwide. Girls reaching adulthood have, on average, lower literacy, education levels, wages, and agricultural productivity compared to men. Meanwhile, the COVID-19 pandemic threatens to exacerbate gender gaps both in adolescence and in adulthood. According to the results ofestimations from a Computable General Equilibrium (CGE) model, reducing gender inequality could potentially increase per capita GDP by up to 13.5 percent by 2050 (i.e., a real rate of return to investment of 9 percent per year) compared to baseline levels. To boost gender equality, the Government should focus on reforms intended to: i) enhance the productivity for adult women; ii) increase learning outcomes for girls; and iii) reduce the prevalence of child marriage and early childbearing.